Caregivers’ Challenges in Delivery of FamilyBased Care to Older Adults in Nigeria - Obiyo, Ngozi; Christy , N. Obikeguna (International Journal of Psychosocial Rehabilitation, 2021)
Global trends and the nature of some people necessitate that they receive some special care. Older adults in Nigeria require such special care. They need family based care. The present study aimed at finding out caregivers’ challenges in delivering family based care to older adults in a Nigerian state. Cross sectional survey design was adopted for this study. 1107 respondents served as the sample size for questionnaire distribution while 12 respondents (comprising of 2older adults and 2 caregivers) was selected from each of the 3 Local Government Areas[LGA] for In-depth interview [IDI]. 48 respondents made up of 24 caregivers and 24 older adults was purposively selected for Focus Group Discussion [FGD], from the three LGAs. This implies 16 (8 caregivers and 8 older adults from each LGA. Thus, the total sample size for the study was 1167 respondents. Descriptive statistics such as percentages and frequency tables were used in presenting the results. The qualitative data were analysed in themes as complement to the quantitative data. The study revealed that caregivers have problems and challenges with caring for older adults. The most reoccurring problems and challenges were financial problems; caregiving is time consuming and older adult’s poor attitude such as lack of appreciation, loss of personal time, and lack of time for social relaxation. Older adult face some challenges and problems from caregivers such as lack of respect, lack of companionship, lack of adequate financial support and their needs not met on time by the caregivers. Caregivers face enormous challenges in the process of caring for older adults, and older adults face challenges from those taking care of them. Caregivers face financial challenges among others. It was recommended that the challenges faced by caregivers can be solved through provision of fund, caregivers also taking care of themselves, more help from relatives and good planning.